2016
DOI: 10.1515/fv-2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Probiotics on Reproductive Parameters of Sows and Health of Their Sucklings

Abstract: Thirtytwo sows were included in the trial. They were divided into the experimental group (n = 16) and a control group (n = 16). The experimental group received 1.28 × 106 Bacillus subtilis and Bacillus licheniformis per gram of feed (400 ppm BioPlus 2B, Chr. Hansen, Denmark). The trial started 2 weeks before farrowing and lasted until weaning. No significant differences were revealed in the number of piglets born alive, stillborn or the number of weaned pigs between the two groups of sows. The wean-to-first se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Nevertheless, commencing the administration of Bacillus spores to pigs post-weaning may not be the most effective strategy. Firstly, it may be too late, as evidence suggests that early-life gut microbiota interventions are more effective (20)(21)(22)(23)(24)(25) . Secondly, the spores may not germinate in the gastrointestinal tract (26) ; and lastly, which may/may not be related to lack of germination, Bacillus administered as spores do not usually persist for more than one week after ceasing administration (12) .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, commencing the administration of Bacillus spores to pigs post-weaning may not be the most effective strategy. Firstly, it may be too late, as evidence suggests that early-life gut microbiota interventions are more effective (20)(21)(22)(23)(24)(25) . Secondly, the spores may not germinate in the gastrointestinal tract (26) ; and lastly, which may/may not be related to lack of germination, Bacillus administered as spores do not usually persist for more than one week after ceasing administration (12) .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported that the stressors that the sows undergo during the perinatal period may be related to the intestinal microbiota (Hayakawa et al, 2016;Cheng et al, 2018). Many studies have reported that the application of probiotics can affect the composition of intestinal microbiota and improve the health and reproductive performance of sows (Alexopoulos et al, 2004;Hayakawa et al, 2016;Link et al, 2016;Tsukahara et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The positive effect of lactic acid bacteria on the growth, health and development of piglets at the weaning age is confirmed byBedford et al (2014) who demonstrated that epidermal growth factor-expressing Lactococcus lactis fermentation product administered to piglets increased their daily weight gain by 54.3 g and decreased feed conversion rate by 0.087 kg. Numerous studies(Taras et al, 2006;Zhang et al, 2020;Lin and Yu, 2020) indicate that probiotic preparations fed to lactating sows also improve the health of piglets Link et al (2016). verified the positive effect of the probiotic containing the spores of Bacillus licheniformis and Bacillus subtilis added to the feed for both piglets and sows.…”
mentioning
confidence: 93%
“…Bernardez et al (2008) and Slivinska and Lukashchuk (2018) argue that the microflora of the gastrointestinal tract in piglets and weaners, and thus their health, are effectively stimulated by probiotics that can be additionally combined with prebiotics. These additives also help reduce the use of antibiotics, thereby decreasing the costs of medical treatment and minimising pig deaths (Bedford et al 2014;Link et al, 2016). In addition, probiotics increase the rate of feed conversion, thus improving the weight gain of animals (Giang et al, 2011;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%